Using an International Experience to Bridge the Gap Between Culture and Science Literacy - Nathan Conner; Jeanette Milius; Christopher T. Stripling; Jamie Loizzo; Debi Doerr (Journal of International Agricultural and Extension Education, 2019)
Today’s agricultural industry is charged with feeding a growing population, which means producing larger quantities of food and marketing the food worldwide. Future employers seek graduates that have global perspectives. To mitigate students’ lack of international knowledge, many higher education institutions are providing students an opportunity to participate in study abroad programs. The purpose of this study was to explore how an international experience in South Africa impacted participants’ perceptions of South African culture, global agriculture, and science. Seven reoccurring themes emerged from the data: a) adaptability (preexperience), b) enhanced communication skills (both pre and post experience), c) an attainment of diverse/broadened academic agricultural knowledge (both pre and post experience), d) risk taking (postexperience), e) intercultural competency and global awareness (both pre and post experience), f) critical thinking skills (postexperience), and g) career enhancement (postexperience). Findings indicate an international experience should integrate cultural learning, academic learning, and should be applied to the participant’s future career.
Keywords: international experiences; science literacy; cultural learning; study abroad